Homofilie Organization of Muhammadiyah Business Charity: Da’wa through Collaboration Brand Network Configuration - Suryorini, Ariana; Savitri, Fania Mutiara; Hartono, Setyo Budi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
Muhammadiyah is a social organization based on the guidelines of the Al-Qur'an & Al-Hadith as the ideology in carrying out all its activities. Internal circles refer to this term as "Islamic purification" which makes it a characteristic of a homophilous organization. This research aims to analyze whether organizational homophily can influence its performance with the Co-BNC novelty. Collaboration Business performance is a strategic da’wa activity. The method used in this research is explanatory quantitative. Amount 35 chief administrators Muhammadiyah Subsidiaries (AUM) in Semarang City who were selected by accidental sampling. The data collection method used was a questionaire method and was processed by Structural Equation Model analysis (SEM) with the AMOS analysis tool. The results of analysis explain: organizational homophily values (Dissemination of Information, Ideas and Emotions) influence marketing performance. In addition, Co-BNC plays a role in mediating this relationship. CO-BNC's success in changing the homophile organization through a brand collaboration approach has brought benefits to many parties, especially those who are "excluded". Harmonization of profit proposition arrangements is carried out by AUM so that mudharib can cover its business to obtain much greater profits/non profit and can remain consistent when AUM restructures its cooperation on business losses. Its shows that the organization stand in survive mode for maslahah and da’wa orientation. We would like to underline that collaboration in business based on values of islamic purification is one form of strategic da’wa activity.